The ability to work remotely: Measures and implications - Kathryn Langemeier; Maria D. Tito (Review of Economic Analysis (REA), 2022)
Our paper explores how the ability to work remotely has changed over time, its relationship with demographic characteristics and employment outcomes, and the role it played during the pandemic recession. We focus on two different remote work indexes, a measure of 'no physical presence'-proposed by Dingel and Neiman (2020)-and a measure of 'remote communications'-presented by Montenovo et al. (2020). While the two measures suggest a similar prevalence of remote work in recent years and display fairly similar behaviors across demographic groups and in terms of wage and employment outcomes, their evolution is significantly different. While the share of occupations that require no physical presence has remained relatively constant since July 2003, the share of those occupations featuring remote communications increased more than 40 percentage points over the same period. Those differing evolutions paint a starkly different picture of the role of remote work during the pandemic: Compared to a counterfactual scenario that keeps the remote classification constant at the 2004 levels for each measure, the index of no physical presence suggests that there would have been little changes in terms of aggregate hours losses during the pandemic, while the index of remote communications points to much larger declines in aggregate hours. Even without much change in the ability of working remotely, the trend towards more remote work underscores the importance of the hours margin as an additional dimension for the realization of gains from working at home.
Keywords: J24; J60; 330; Remote Work; Work from Home; Hours Worked; Pandemic Recession; Covid-19